Social cohesion and carbon emissions - Ramos-Toro, Diego (Munich, 2017)
"This paper demonstrates that population diversity and its adverse effect on social cohesion have a robust, causal, positive effect on the carbon emissions of sufficiently rich economies. An examination of geocoded data on emissions from fossil fuels reveals that such results holds at a subnational level as well. The documented effect of diversity operates through its impact on mistrust and on heterogeneity in preferences, which suggests a social dimension that must be contemplated when setting a strategy to curb human’s carbon footprint."